Competition kinetics using the UV/H2O2 process: a structure reactivity correlation for the rate constants of hydroxyl radicals toward nitroaromatic compounds - Garcia Einschlag, Fernando Sebastian (2003)
The rate constants for hydroxyl radical reaction toward a set of nitroaromatic substrates kS, have been measured at 25ºC using competition experiments in the UV/H2O2 process. For a given pair of substrates S1 and S2, the relative reactivity beta(defined as kS1/kS2) was calculated from the slope of the corresponding double logarithmic plot, i.e., of ln[S1] vs. Ln[S2]. This method is more accurate and remained linear for larger conversions in comparison with the plots of ln[S1] and ln[S2] against time. The rate constants measured ranged from 0.33 to 8.6 109 M-1 s-1. A quantitative structure–reactivity relationship was found using the Hammett equation. Assuming sigma values to be additive, a value of -0.60 was obtained for the reaction constant rho. This value agrees with the high reactivity and the electrophilic nature of HO•.radical.